Establishment of a reverse genetics system for SARS-CoV-2 using circular polymerase extension reaction - Torii, Shiho; Ono, Chikako; Suzuki, Rigel; Morioka, Yuhei; Anzai, Itsuki; Fauzyah, Yuzy; Maeda, Yusuke; Kamitani, Wataru; Fukuhara, Takasuke; Matsuura, Yoshiharu (Cell reports (Cambridge), 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been identified as the causative agent of coronavirus disease 2019 (COVID-19). Although multiple mutations have been observed in SARS-CoV-2, functional analysis of each mutation of SARS-CoV-2 has been limited by the lack of convenient mutagenesis methods. In this study, we establish a PCR-based, bacterium-free method to generate SARS-CoV-2 infectious clones. Recombinant SARS-CoV-2 could be rescued at high titer with high accuracy after assembling 10 SARS-CoV-2 cDNA fragments by circular polymerase extension reaction (CPER) and transfection of the resulting circular genome into susceptible cells. The construction of infectious clones for reporter viruses and mutant viruses could be completed in two simple steps: introduction of reporter genes or mutations into the desirable DNA fragments (∼5,000 base pairs) by PCR and assembly of the DNA fragments by CPER. This reverse genetics system may potentially advance further understanding of SARS-CoV-2. [Display omitted] •A quick PCR-based reverse genetics system is established for SARS-CoV-2•SARS-CoV-2 recombinants harboring reporter genes or mutations can be generated Torii et al. establish a novel PCR-based, bacterium-free reverse genetics system for SARS-CoV-2 using the CPER method. Recombinant SARS-CoV-2 can be produced with high titers around 2 weeks after amplification of SARS-CoV-2 gene fragments. The method can be applied to generate recombinant SARS-CoV-2 carrying reporter genes or mutations.